PREVALENSI ANAK KESULITAN BELAJAR di SEKOLAH DASAR NEGERI Se-KECAMATAN KURANJI PADANG - NOVIANA - (Universitas Negeri Padang, 2015)
This research was conducted based on the problems found in Elementary School showing that the students with learning difficulties got problems to read, write and calculate. In this case, the teachers and the headmasters did not yet discover the number of the students having learning difficulties in Elementary School from the first grade to the second grade surely. The local Ministry of Education also did not perceive the number and the data of the students with learning difficulties especially those living in Kecamatan Kuranji. The purpose of this research was to reveal the prevalence or the number of the students having problems to read, to write or to calculate in Elementary Schools in Kecamatan Kuranji Padang. This research applied descriptive method and quantitative approach. The sample was chosen by using purposive sampling technique. The data were gathered by using questionnaire and were analyzed by using percentage formula. Based on the results of the research , it was figured out that the number of the students having problems to read in 53 Elementary Schools in Kecamatan Kuranji Padang was 2.973 or 23.4% of 12.762 students. The number of the students having problems to write in 53 Elementary Schools in Kecamatan Kuranji Padang was 3.062 or 24.1% of 12.762 students . The number of the students having problems to calculate in 53 Elementary School in Kecamatan Kuranji Padang was 3.530 or 28% of 12.762 students.Keywords : Prevalence ; students with learning difficulty; descriptive quantitative.